A systematic review of additive manufacturing-based remanufacturing techniques for component repair and restoration. (3rd March 2023) - Kanishka, Kumar; Acherjee, Bappa
Abstract: Remanufacturing, the process of transforming end-of-life and end-of-use components into reusable ones, is gaining prominence as one of the essential elements for achieving resource-efficient industrial sectors and a circular economy. Additive manufacturing (AM) has emerged as an enabling technology for the automated repair and restoration of worn-out products, especially for high-value parts, to as-new conditions for the following life cycle. This paper offers a comprehensive analysis of the foundational principles and prospective applications of additive manufacturing technology for product restoration and repair. The primary goal of this review is to consolidate the discrete information to present a comprehensive picture of the worldwide scenario for the advancement and use of AM-based repair and restoration in remanufacturing applications. Although the focus of this review is primarily on the state-of-the-art in additive remanufacturing — principles, strategies, qualities, practices, and applications, it also includes reverse engineering applications in additive remanufacturing and decision support frameworks for additive remanufacturing. The conclusion of the review and the prospects for further research work are eventually addressed. Highlights: A systematic review of component remanufacturing using additive manufacturing Development and deployment of AM-based repair and restoration in remanufacturing applications State-of-the-art in additive remanufacturing principles, strategies, qualities, practices, and applications Decision support frameworks and reverse engineering in additive remanufacturing